Development and survival of Triatoma barberi and Triatoma longipennis (Hemiptera: Reduviidae) is Affected by Trypanosoma cruzi Colonization - Becerril-Flores, Marco Antonio; Benítez-Hernández, Ana Karen; Santos-Castañeda, Antonio; Tovar-Tomás, María del Rosario; Molina-Trinidad, Eva María (Revista Colombiana de Entomología, 2024)
Triatomines are insect vectors of the flagellate protozoan Trypanosoma cruzi, the causative agent of Chagas disease. This occurs when the triatomine defecates on the skin of the vertebrate host when it bites its host for feeding. This lesion causes the penetration of T. cruzi, whose infective phase is the tripomastigote, and the non-infective replicative phase epimastigote. Although the effects of T. cruzi on the development and survival of different species of triatomine bugs are known, it has not been fully described how the parasite affects many of the species that inhabit Mexico. Therefore, the present study aimed to investigate the effect of the presence of T. cruzi on triatomine development and survival. For this, five triatomines of each instar of each species, Triatoma barberi and Triatoma longipennis, were inoculated, from their second instar to their adult stage, female or male. Each triatomine was infected with 3-5 x105 parasites and they were incubated for 100 days and the kinetic of parasites in the feces and T. cruzi phases were recorded. The results showed that T. barberi and T. longipennis development was affected in all stages because of T. cruzi infection. It was greater for T. longipennis, both in its mortality, as well as time to molt in each phase.